Modelar Molecular das interações do complexo NS1/anti-NS1 para aplicação no diagnóstico diferencial de Flaviroses - Guerra, Renan Faria (2021)
The development of differential diagnosis methods between Dengue and Zika Flaviviruses, which overcome cross-reactivity, is a challenge that finds in imunosensors a promising alternative due to its greater selectivity and specificity. In this work, molecular modelling methods were used to understand and elucidate, in silico, specific molecular interactions of nonstructural 1 protein (NS1) and antibody anti-NS1 complexes, required by these devices. The MD simulations suggested energetic and structural stability of the anti-NS1 antibody and the NS1 protein, even in the absence of glycosylation, and allowed the statistical sampling of their representative structures in aqueous environment with good stereochemical quality. The NS1 proteins and antibody structures were submitted to the Molecular Docking protocol to predict 3D structure of near-native complexes. The proposed protocol combines rigid body Molecular Docking with different pose prediction methods, CAPRI evaluation criteria, search for epitope amino acids residues and semiempirical approach, and presented better performance for systems studied with crystallographic ligand and receptor input files. From its application, the most representative models of each studied system were predicted by ClusPro webserver and selected considering the higher number of conserved epitopes residues in the PPIs characterized by a higher number of hydrogen bonds, hydrophobic and p-p intermolecular specific interactions. Therefore, these models were described as the most representative models of antigen-antibody specific interaction. The wing and b-leader domains were, respectively, the preferential interaction region of the antibody with NS1-DENV2 and NS1-ZIKV proteins. Furthermore, binding free energy values ranges from -6.5 to -13.0 kcal mol-1, which is usual for this kind of complexes, and dissociation constants (Kd) in different magnitude orders (10-8 to 10-10 M) suggested selectivity and specificity for the studied systems, with potential application in sensoring devices, in particular AFM-type sensors, for differential and early diagnosis of Dengue and Zika.